2008
DOI: 10.4028/www.scientific.net/msf.584-586.661
|View full text |Cite
|
Sign up to set email alerts
|

Properties of UFG HSLA Steel Profiles Produced by Linear Flow Splitting

Abstract: Abstract. Linear flow splitting is a new cold forming process for the production of branched sheet metal structures. It induces severe plastic strain in the processing zone which results in the formation of an UFG microstructure and an increase in hardness and strength in the flanges. Inbuilt deformation gradients in the processing zone lead to steep gradients in the microstructure and mechanical properties. In the present paper the gradients in the UFG microstructure and the mechanical properties of a HSLA st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Neither the flange angle α nor the flange thickness sf or the sheet thickness s0 seem to have a strong effect on the resulting distribution of mechanical properties. For all LFS parameters and materials investigated in this work or previously [13,[20][21][22][23], the gradients are very similar exhibiting a steep decrease in hardness with increasing distance to the split surface to a depth of 300 to 500 µm and a flatter decrease or even constant hardness down to the lower side of the flange. This gradient correlates with a decrease in HAGB fraction and aspect ratio as well as an increase in grain size.…”
Section: Characteristic Properties In Lfs and Lbs Profilessupporting
confidence: 51%
“…Neither the flange angle α nor the flange thickness sf or the sheet thickness s0 seem to have a strong effect on the resulting distribution of mechanical properties. For all LFS parameters and materials investigated in this work or previously [13,[20][21][22][23], the gradients are very similar exhibiting a steep decrease in hardness with increasing distance to the split surface to a depth of 300 to 500 µm and a flatter decrease or even constant hardness down to the lower side of the flange. This gradient correlates with a decrease in HAGB fraction and aspect ratio as well as an increase in grain size.…”
Section: Characteristic Properties In Lfs and Lbs Profilessupporting
confidence: 51%
“…Nevertheless it imposes severe strains and produces an ultrafine grained (UFG) microstructure in a surface layer [5]. The process zone is less defined than in the previously mentioned SPD processes and exhibits steep strain gradients [6], leading to strong microstructure and yield strength gradients in the flange thickness direction [7]. Earlier investigations using electron backscattering diffraction (EBSD) have shown that the crystallographic texture also varies along with the other gradients [8].…”
Section: Introductionmentioning
confidence: 97%
“…The heterogeneous material flow in the process zone leads to the development of characteristic microstructure and yield strength gradients in thickness direction of the produced flanges, Fig. right . At the split surface, i.e.…”
Section: Introductionmentioning
confidence: 99%